(untitled) (Perner’s Contacts, 2011)
This article describes multilateration surveillance systems and their impact on increase in capacity and safety of air traffic. The work includes a description of multilateration systems and used methods of signal processing – central and distributed time architecture. Conclusion of this work deals with multilateration systems in various flight phases and their benefits for flight.